Mexico : Land Policy--A Decade after the Ejido Reform - World Bank (Washington, DC, 2013)
This study aims to assess the extent to which reforms have actually been implemented, the impact they have had on the rural population, and the challenges which, as a consequence, need to be addressed by the new administration. This report is organized as follows: Section 1 describes Mexico's rural economy. It reviews the broad context of macro, trade, and sector-level reforms, the strengths and weaknesses of both the productive and socio-economic structure of agriculture and the social sector, highlighting in particular the socio-economic and natural resource characteristics that make the ejido sector central to Mexico's development. Section 2 details the rationale behind the 1992 legal reforms intended to to end almost a century of politically motivated interventions in the internal structure of te ejido and improve the functioning of land and labor markets in the social sector. This section reviews the way reforms were implemented, the procedural safeguards adopted to prevent abuse, and the advances, both in terms of numbers as well as impact, made in implementing them. Section 3 assesses PROCEDE (the National Certifcation Program of Ejido Rights and Urban Lots) and its impact on the functioning of land rental and sales markets, ejidatarios' access to credit, and investment. Section 4 sums up policy recommendations in six key areas, including land policy, completion of PROCEDE, and ensuring the sustainability of the advances made under PROCEDE.